PENGARUH INTELLECTUAL CAPITAL STRUKTUR MODAL DAN TINGKAT INFLASI TERHADAP KINERJA KEUANGAN PERBANKAN SYARIAH DI INDONESIA - Putri Indriani; Nirdukita Ratnawati (Media Ekonomi, 2017)
The purpose of this study was to analyze the relationship and the influence of Value Added Intellectual Capital (VAIC) and Structure of capital as measured by Capital Adequacy Ratio (CAR) and The Rate of Inflation on financial performance Islamic Banking. The method used in this study is the regression method panel. The data used in this study were taken from the nine Islamic Bank in Indonesia Indonesian period 2010-2015. Results of the study showed inflasi have positively to financial performance and CAR have negatively to financial performance. If seen from the results an VAIC on financial performance have the positively significant results at Islamic bank in Indonesia .